KARAKTERISTIK SPASIAL TEMPORAL KONDISI OSEANOGRAFI LAUT BANDA DAN HUBUNGANNYA DENGAN POTENSI SUMBERDAYA PERIKANAN - Wijaya, Adi; Priyono, Bayu; Mahdalena, Nadya Christa (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2018)
The Banda Sea is an area of water with a high potential in the field of fisheries. The condition is indicated by high fishing season. This paper aims to examine the relationship between physical oceanographic conditions with tuna, tuna and skipjack catch landed at the Ambon Fishing Port (PPN) of Ambon in 2015. The data used are monthly average monthly data of INDESO model of the model which includes temperature, salinity and current with 1/12-degree spatial resolution. Based on data of tuna fish caught at temperature range 16-18 0C, salinity 34-34,5 PSU, current 0,1-0,05 m/s at >200 m deep; tuna fish caught at temperature range 20-22 0C, salinity 34-34,5 PSU, current 0,1-0,05 m/s at depth <100 m; and skipjack caught at temperature range 29,5-31 0C, salinity 31-33 PSU, current 0,15-0,30 m/s at depth <100 m. The results showed that the conditions of temperature, salinity and current vertically in the Banda Sea at depths of <100 and >200 m, showed an increase in a catch during the transition period II (September-November) and the west season, while in the transition season I (March-May) and the east has decreased.